Pengembangan Media Bergambar Berseri Untuk Meningkatkan Keterampilan Berbahasa Indonesia Siswa Kelas III pada Pembelajaran Daring di SDN 102025 Rambung Sialang Sawit - Antika, Rindi; Bahri, Samsul (Institut Teknologi Pendidikan Indonesia, 2022)
This research is motivated by the ability of students who are still very lacking in using language spelling and in developing sentences. This is indicated by the achievement of the KKM of 22 students who can reach the KKM only 22% in language, while those who have not reached the KKM are 78%. One of the reasons is that teachers have not used learning media so students are less enthusiastic about learning and look passive because learning looks monotonous. This causes low student learning outcomes. To improve language learning in the classroom, serial picture media are used as an effort to stimulate students to be active and enthusiastic in participating in learning. The purpose of this study was to develop serial image media and test its effectiveness in improving students' language skills. This type of research is the Research and Development (R&D) method. The design in this study used the Pretest and Posttest Design. The subjects in this study were grade III students at SDN 102025 Rambung Sialang Sawit, totaling 22 students. Data collection techniques used are questionnaires, interviews, and documentation. The results showed that there was an increase in students' writing results before and after the use of serial picture media. This is indicated by an increase of 0.43 which was tested using the normalized gain test. In addition, there is a comparison of t-count and t-table with the t-test test (left side) obtained tcount = 42,709 with = 5% then t-table = 21. Thus it can be concluded that the use of serial image media can improve students' language skills at SDN 102025 Rambung Sialang Sawit.